The importance of circumstance: Digital access and affordability for people experiencing homelessness - Humphry, Justine (Journal of Telecommunications and the Digital Economy, 2020)
Access to and affordability of digital technology for vulnerable and disadvantaged groups is an ongoing concern in an Australian context, however the digital needs, issues and barriers for consumers who are homeless are largely neglected in this literature. This paper presents findings from a research project on mobile phones and the internet in the lives of people experiencing homelessness and engages with some key issues of digital exclusion arising in the context of a general shift in connectivity to mobile media and the push by the Australian government to reform service provision around these changes. The paper argues for the need to recognise the ways that life situations and circumstances of hardship, such as homelessness, factor into the patterns of mobile and Internet connectivity, creating unique issues of digital access and equity. It argues for knowledge of these differences to inform digital delivery of government services and approaches to telecommunications policies and assistance programs, and puts forward a number of recommendations based on a study of 95 adults, families and young people experiencing homelessness which was carried out in Sydney and Melbourne in early 2014.